2022
DOI: 10.3389/fpsyg.2022.867945
|View full text |Cite
|
Sign up to set email alerts
|

Defining Power and Agency in Gender Relations in El Salvador: Consequences for Intimate Partner Violence and Women’s Mental Health

Abstract: Intimate partner violence (IPV) affects thousands of women around the world and is prevalent in the Global South. Unequal social structures perpetuate hierarchies and maintain women’s vulnerability to violence. Difficulties women face in accessing education, economic resources, and employment diminish their power in intimate relationships, increasing the likelihood of IPV. These factors can also have a significant effect on women’s mental health. However, some studies show that economic empowerment does not ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Previous studies from several African, Asian, and Latin American countries have reported various IPV correlates [1][2][3][4][5][9][10][11][12][13][14][15][16][17][18][19][20][21][22]24,26 ; in this secondary analysis 12 correlates at the level of individual respondent, husband/partner, and familial levels were studied in terms of association with respondent having ever experienced any form of intimate partner violence. These included women's' age, women's and her husband's/partner's educational attainment, women's occupation, household's wealth index, residential status (urban or rural), number of living children, decision making, IPV acceptance, husband's/partner's alcohol use, having ever witnessed one's father physically beating up one's mother, and marital control.…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from several African, Asian, and Latin American countries have reported various IPV correlates [1][2][3][4][5][9][10][11][12][13][14][15][16][17][18][19][20][21][22]24,26 ; in this secondary analysis 12 correlates at the level of individual respondent, husband/partner, and familial levels were studied in terms of association with respondent having ever experienced any form of intimate partner violence. These included women's' age, women's and her husband's/partner's educational attainment, women's occupation, household's wealth index, residential status (urban or rural), number of living children, decision making, IPV acceptance, husband's/partner's alcohol use, having ever witnessed one's father physically beating up one's mother, and marital control.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…9,10 Plethora of IPV correlates have been reported using DHS and other data: these include gender-based power differentials with women experiencing limited empowerment and autonomy in terms of making or contributing to personal or household decisions, acceptance of IPV, low educational attainment by women or her partner, alcohol use by the partner, age of women, age of partner, and marital control displayed by the partner. 11-18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of statistically significant association with the educational attainment of the respondent or her intimate partner was another unusual finding from this study. Several studies have reported an association of IPV with women’s low educational attainment and that of their partners ( 5 , 13 , 18 , 22 ); conversely, higher educational attainment was found to serve as a protective factor against IPV ( 5 , 19 , 21 , 23 , 26 ). Even parental educational attainment of less than high school has been associated with IPV ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, the correlates associated with IPV tend to underscore low educational attainment by both partners, low socioeconomic status, use of alcohol by male partner, physical power differences, attitudinal acceptance of violence in the context of intimate relationships by women, rural residency status; all conspiring against the backdrop of deeply entrenched patriarchal cultures, traditional family values emphasizing harmony and ideological pressures to preserve marriages, force women to remain imprisoned in abusive relationships [3,4,14,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%